Perancangan Sistem Pemantauan Kelelahan Driver Berbasis IoT (Internet Of Things) Yang Adaptif Untuk Transportasi Makanan Segar: Studi Kasus Di Industri Logistik - Miftahol Arifin; Dimas Fanny Hebrasianto Permadi Kasanah; Pradana Ananda Raharja; Nabila Noor Qisthani; Fikra Titan Syifa; Faizah Faizah (Jurnal Kendali Teknik dan Sains, 2023)
In the logistics industry, fresh food transportation requires effective management of driver fatigue to maintain safety and service quality. With the increasing digital connectivity, Internet of Things (IoT) technology has become a promising solution to monitor driver fatigue in real-time. This research aims to design an adaptive IoT-based driver fatigue monitoring system specifically for fresh food transportation. Through a case study in the logistics industry, we identified specific challenges and needs in driver fatigue management. Based on the identification results, we developed a system that utilizes IoT sensors integrated in vehicles and drivers' smartphones. The system automatically monitors the driver's physical condition and behavior and provides real-time alerts if signs of fatigue are detected. With an adaptive approach, the system can customize recommendations and interventions according to the measured fatigue level. The results of the case study show that the designed system is able to reduce the risk of driver fatigue, increase transportation safety, and improve service quality in fresh food transportation. This research contributes to the practical understanding of the implementation of IoT technology in driver fatigue management, particularly in the context of the logistics and fresh food transportation industries.